DIFFERENTIATION AND BALANCE OF MINERALS DURING TRANSFORMATION OF THE OPEN SURFACE OF ARABLE SOILS UNDER THE IMPACT OF RAIN - E. Yu. Prudnikova; E. B. Varlamov; N. A. Churilin; A. E. Churilina (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
During the model experiment the changes in the mineralogical composition of the open surface of arable soil (leached chernozem, gray forest soil, sod-podzolic soil) under the impact of raindrops under fallow conditions were studied. At the end of the experiment a mineralogical analysis of individual particle size fractions < 1, 1–5, 5–10 and > 10 μm from microcrusts formed on open surfaces and a soil substrate not exposed to the effects of precipitation was conducted. The study found that during the exposure there was redistribution and changes in the proportional ratios of the contents of different particle size fractions and associated clay and clastogenic minerals. During the experiment the most significant changes due to their composition occurred in the sample of sod-podzolic soil and leached chernozem. The content of clay minerals in exposed samples decreased the most. The redistribution of clastogenic minerals from the upper open layer, mostly from fine silt and to a lesser extent from the middle silty fraction, was accompanied by a relative accumulation of the fraction > 10 μm. The redistribution of granulometric fractions was accompanied by a relative accumulation of quartz, orthoclases and a decrease in the content of chlorite and biotide in them. Such a distribution is determined by their resistance to weathering. Balance calculations allowed establishing that the total losses of clay and clastogenic minerals from the upper open surface of the monoliths in comparison with the initial soil substrate were more than 4 kg / 100 kg of monolith for gray forest soil, 16 kg / 100 kg of monolith for leached chernozem and 46 kg / 100 kg of monolith for sod-podzolic soil.